Reforming agricultural subsidies for improved environmental outcomes - Mamun, Abdullah; Martin, Will; Tokgoz, Simla (Food and Land Use Coalition, 2019)
The fifty-one developed and developing countries covered by the OECD’s 2018 agricultural policy monitoring and evaluation provided $483 billion per year in 2015-17 in support to farmers (OECD 2018, p105) and an additional $86 billion on services such as agricultural innovation, infrastructure and stockholding. Most of the $483 billion in support is provided by trade measures that raise (or lower) the prices received by farmers relative to world prices, with the remainder provided by subsidies. While agriculture has many environmental impacts, we focus on emissions of greenhouse gases (GHG) because of their global impact and their potentially catastrophic consequences for the world, and for agriculture in particular. With agricultural production and land use change contributing close to a quarter of global GHG emissions, this spending has potentially large implications for greenhouse gas emissions and hence for climate change. However, the magnitude and even the direction of these policy impacts is uncertain, making analysis essential for well-founded policy recommendations.